Histological Characteristics of Non-alcoholic Steatohepatitis in NAFLD Patients With Low Degree of Hepatocyte Apoptosis - Ma, Hong-Lei; Zheng, Kenneth I.; Rios, Rafael S.; Tang, Liang-Jie; Li, Gang; Zhu, Pei-Wu; Wang, Xiao-Dong; Chen, Yong-Ping; Zheng, Ming-Hua (Turkish Journal of Gastroenterology, 2021)
Background: Caspase-cleaved K18 (cK18) may accurately reflect hepatocyte apoptosis in patients with non-alcoholic steatohepatitis (NASH). However, NASH can also exist within the normal range of cK18. The aim of this study was to investigate the risk factors and characteristics of NASH within the normal serum levels of cK18. Methods: In the study, 227 histopathologically confirmed non-alcoholic fatty liver disease (NAFLD) patients with normal cK18 levels (≤200 U/L), measured in serum using ELISA kits, were enrolled. The Rs738409 allele, coding patatin-like phospholipase domain-containing protein 3 (PNPLA3), was detected by MALDI-TOF mass spectrometry. Non-alcoholic steatohepatitis was defined as an NAFLD activity score (NAS) ≥5 with each part >0. Results: The prevalence of NASH was 31.7% among NAFLD patients with normal serum cK18 levels. Compared with non-NASH, NASH had a higher possibility of occurrence with central obesity, insulin resistance, and the G allele of PNPLA3. The mean serum levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were higher in NASH patients. Moreover, ALT, AST, TC, LDL-C, central obesity, and the PNPLA3 G allele were risk factors for NASH in NAFLD patients with normal serum cK18 levels, with odds ratios of 1.01 (95% CI: 1.00, 1.02), 1.03 (95% CI: 1.01, 1.05), 1.33 (95% CI: 1.04, 1.68), 1.41 (95% CI: 1.03, 1.92), 2.19 (95% CI: 1.15, 4.18), and 2.48 (95% CI: 1.15, 5.36), respectively; all P < .05. Conclusions: The major risk factors for NASH were central obesity, AST, and the PNPLA3 G allele, in NAFLD with low hepatocyte apoptosis.